2017
DOI: 10.1002/2016jb013341
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of structure and permeability of normal faults with clay smear: Insights from water‐saturated sandbox models and numerical simulations

Abstract: Clay smear is difficult to predict for subsurface flow applications and would benefit from an improved understanding of the processes controlling clay smear. We present water‐saturated sandbox experiments with large clay smear surfaces (~500 cm2) that couple cross‐fault fluid flow measurements with structural analysis of excavated clay smears. We compare measured flow data to numerical flow simulations to develop a tool to evaluate the evolving fault structure. Results show diagnostic relationships between fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The main goal of this work is providing new insight on the impact of stratigraphically-consistent fault material arrangements with clay smears on fault permeability. In § 3 in the main text we validate PREDICT with cm-scale experiments by Kettermann et al (2017), and we also compare our results to those from Sperrevik et al (2002)'s permeability predictor and other laboratory and field measurements in similar geology. A multi-scale, 3-component validation of PREDICT's output requires quantifying the mismatch between the permeability distributions and measurements of the macroscale fault permeability in m-to km-scale faults.…”
Section: Nomenclaturementioning
confidence: 71%
See 2 more Smart Citations
“…The main goal of this work is providing new insight on the impact of stratigraphically-consistent fault material arrangements with clay smears on fault permeability. In § 3 in the main text we validate PREDICT with cm-scale experiments by Kettermann et al (2017), and we also compare our results to those from Sperrevik et al (2002)'s permeability predictor and other laboratory and field measurements in similar geology. A multi-scale, 3-component validation of PREDICT's output requires quantifying the mismatch between the permeability distributions and measurements of the macroscale fault permeability in m-to km-scale faults.…”
Section: Nomenclaturementioning
confidence: 71%
“…• Along-strike smear segment number (s s ): This parameter defines the segmentation of smears in the strikeparallel direction, and is based on the hole mappings in excavated fault surfaces by Kettermann et al (2016Kettermann et al ( , 2017; Noorsalehi-Garakani et al (2013). We counted the number of holes along strike-parallel, horizontal lines of length equal to f D to define the maximum and minimum number of holes (N h ).…”
Section: S121 Marginal Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fault-related processes, such as clay smear (Vrolijk et al 2016), can drastically influence permeability of a fault, e.g., by acting as a barrier to fluid flow. The existence of clay smear alone, however, is not a defining indicator on the permeability of the fault, as potential breaching of the clay layer coincides with increased flow across the fault (Kettermann et al 2017). Furthermore, experimental data showed that the influence of clay smear on permeability changes with fault activity, i.e., rock deformation (Takahashi 2003).…”
Section: Discussionmentioning
confidence: 99%
“…in faulted deposits, and by sedimentary structures as shown by Lapperre et al (1996) who studied heterogeneity using hydraulic conductivity measurements on 271 undisturbed core samples taken in horizontal, vertical and 'structure' direction. Based on water-saturated model experiments (Schmatz et al, 2010) and multiple experiments using a water-saturated sandbox to simulate clay smear, Kettermann et al (2017) concluded that flow patterns under these circumstances are complex and three-dimensional. Vertical temperature profiles in nests of piezometers in unconsolidated sedimentary aquifers in the German opencast lignite mining area also indicate fault zone heterogeneity.…”
Section: Fault Zone Permeability and Heterogeneitymentioning
confidence: 99%